Old ages of two historical Romanian trees assessed by AMS radiocarbon dating - Patrut, Adrian; von Reden, Karl F.; Lowy, Daniel A.; Patrut, Roxana T.; Vaida, D. Lucian; Margineanu, Dragos (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions with Materials and Atoms, 2013)
Two large Romanian poplars are considered to be associated with significant historical events of the past. In order to verify these claims, wood samples collected from the broken trunks of the two poplars were radiocarbon dated by AMS. The oldest radiocarbon dates were found to be 275 +/- 20 bp for the black poplar of Mocod and 316 +/- 22 bp for the gray poplar of Rafaila. These values correspond to calibrated ages of 365 +/- 10 and 465 +/- 25 years, respectively. The dating results indicate old ages for the two trees, i.e., 455 years for the Mocod poplar and 560 years for the Rafaila poplar. Such age values validate historical information on the two large Romanian trees. (C) 2012 Elsevier B.V. All rights reserved.
id: 2245; PT: J; CT: 12th International Conference on Accelerator Mass Spectrometry (AMS); CY: MAR 20-25, 2011; CL: Wellington, NEW ZEALAND; TC: 0; UT: WOS:000313234300119